Designing of community-based conservation and breeding program for Begaria cattle breed found in Arid and Semi-Arid areas of Benishangul Gumuz region of Ethiopia - Ayele, Tesfalem; Getachew, Tesfaye; Banerjee, Sandip; Melak, Awoke; Belayhun, Teklewold; Engdawork, Aweke; Kefyalew, Esho; Assefa, Abraham; Hailu, Abebe (Elsevier, 2023)
The objectives of the study were to design appropriate community-based conservation and breeding programs for the identified breeding objective traits of Begaria cattle breed. Seven alternatives (5%, 10%, 20%, 25%, 50%, 75%, and 100% of the total cow population) were considered for 20-year investment periods. In the current alternatives, the burden of record keeping in the dispersed villages, the effect of inbreeding, and the possibility of including the entire population in the improvement work were taken into consideration. Alternative breeding programs were simulated using ZPLAN software. Input parameters like population, biological, phenotypic standard deviation, costs, and economic values of objective traits were estimated. Pooled heritability and pooled phenotypic standard deviations were applied. A bio-economic model developed in a Microsoft Excel spreadsheet was used to estimate the economic weight of the traits of interest. Higher values of predicted genetic gains were observed for the breeding objective traits of age at first calving (AFC), lactation milk yield (LMY) and yearling weight (YW) with values ranging from −1.93 to −1.95, 1.13 to 1.14 and 1.30, respectively, and lower values for the calving interval (CI) and survival rate (SUR). Likewise, higher returns were observed for YW, AFC and LMY with values of (euro) 4.69–10.88, 4.08 to 9.47 and 2.66 to 6.17, respectively, and lower values were reported for CI and SUR. Positive and incremental total returns and profits were observed across the breeding unit size, with values ranging from 11.67 to 27.09 and 3.94 to 25.17, respectively. From a profit and total return point of view, the 100% breeding unit size was more attractive. However, with regard to annual monetary genetic gains, genetic merit for each objective trait, and the burden of record keeping, a 25% breeding unit size could be ideal.